Instagram jako narzędzie w procesie uczenia się języka włoskiego jako obcego - Kolbus, Zuzanna (Pedagogika Społeczna Nova, 2024)
The aim of this article is to present a comparative analysis of the content created and shared by Polish promoters of the Italian language through the social media platform Instagram. The analysis covered 60 accounts run by Polish creators. The collected material pertains to profiles of individuals, language schools, student societies, and other organisations promoting Italian studies in Poland. Based on the gathered data, the author attempts to answer the question of what Instagram offers to learners of Italian and how it can impact their language competence.